COMPARATIVE STUDY OF SOME FEEDS FOR MAGUR CLARIAS BATRACHUS LINN.FRY (Biological Sciences - PJSIR, 2022)
Magur (Clarias batrachus) fry were reared for a period of twelve days in plastic bowl to determine the effect ofdifferent feeds (live plankton, frozen plankton, dried plankton and Tubifex) on survival rate and growth. Survival wasfound to be comparatively higher with live Tubifex and live plankton. Greatest length (13.0 mm) was obtained withTubifex and least (11.0 mm) with dried plankton.